Exploring the Efficacy of Natural Remedies vs. Chemical Interventions in Dental Caries Management : A Comprehensive Meta-Analysis - Mohamad Daffa Yuansyah; Ghani Phalosa; F. Josse Pasca Pradana (Indonesian Journal of Multidisciplinary on Social and Technology, 2026)
Dental caries remains a major oral health problem, particularly in Indonesia, and requires effective preventive and therapeutic strategies. This meta-analysis compared natural remedies with chemical interventions for managing dental caries and reducing Streptococcus mutans populations. The review followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines and included randomized controlled trials published from 2018 to August 2023. Searches were conducted in PubMed, Cochrane, Scopus, and Epistemonikos using predefined PICO criteria. Eligible studies evaluated chemical interventions, including fluoride, chlorhexidine, and probiotics, or natural ingredients, including gum arabic, green tea, and miswak. Risk of bias was assessed using the Cochrane RoB 2 tool, while pooled effects were analyzed with Review Manager using fixed- or random-effects models according to heterogeneity. The findings showed that chemical interventions produced an overall significant reduction in dental caries incidence, with fluoride demonstrating the strongest and most consistent evidence. Probiotics significantly reduced Streptococcus mutans populations, whereas chlorhexidine showed favorable but less conclusive effects. Natural remedies also demonstrated preventive potential: gum arabic and green tea reduced caries incidence, while gum arabic and miswak significantly reduced Streptococcus mutans populations. Nevertheless, substantial heterogeneity and differences in intervention protocols limited direct comparison. A combined approach integrating evidence-based chemical therapy with promising natural remedies may provide comprehensive caries management. Larger, well-designed clinical trials are required to establish optimal dosages, application frequencies, long-term effectiveness, and safety.